(untitled) (Semiárida, 2020)
Fire may be reintroducted as prescribed burns for different purposes, mainly to remove accumulated fuels and the risk of intense fires or as a tool of range management in order to improve the forage offer. The objective of this study was to assess the vegetation response to burning 6 and 12 months after precribed fires in two different caldén woodlands: open woodland (BA) associated with torage species, and closed forest (BD) with a poor proportion of forage species a) in the community b) in the seed bank. The effect of prescribed burn in this study had less impact on the vegetation structure of both communities than expected, in terms of reduction of non palatable woody species and increasing of forage species abundance. The vegetation response is principally influenced by ils structural and floristic characteristics.